(untitled) (Cadernos de Sociomuseologia, 2017)
This paper analyses the studies that exist on the development of cultural heritage in Bahia via processes of musealization within the context of Museology, affiliated with the GP Bahia Museology Observatory, in the field of the History of Museology in Bahia (Department of Museology/PPG Museu/FFCH/UFBA – CNPq). Issues relating to research, the field of museology and cultural heritage in Bahia are evaluated based on the hypothesis that exhibits, museums and collections (both public and private) contributed to the development of support platforms for the construction of this heritage. The objective is to identify the variables, participants and entities that were involved in this historic process. The methodology based on the identification, cross-referencing and analysis of sources of information has brought to light details regarding Bahian institutions and personalities that are a response to local social and cultural demands. Finally, an overview is presented of the studies currently available to provide support to the paper’s historiographic focus. Keywords: museology, exhibits, museums, collections, history of Museology in Bahia.